Female body size, weight and fat storage rather than nestmateship determine male attraction in the invasive yellow-legged hornet Vespa velutina nigrithorax. Issue 1 (2nd January 2019) - Cappa, Federico; Cini, Alessandro; Pepiciello, Irene; Petrocelli, Iacopo; Cervo, Rita
Abstract : In the early stage of the invasion process, alien species may face costs linked to pioneer effect due to genetic bottleneck, drift and the consequential inbreeding depression. Thus, introduced species that show an immediate exponential growth in their invasive population should have some mechanisms to reduce such costs minimising the chance of inbreeding or allowing them to cope with them. The yellow-legged hornet Vespa velutina nigrithorax has been spotted in France in 2004; since then, the species has been invading Europe with a relentless pace. In their native range, males and reproductive females of a Chinese non-invasive sub-species of V. velutina seem to leave their nests to search for unrelated partners. However, previous studies showed a low genetic diversity and a high rate of diploid males in colonies of the invasive population, suggesting that mating could occur inside nests, where males should be able to discriminate between reproductive gynes and sterile workers. Here, we used laboratory behavioural assays to investigate the mating preferences of yellow-legged hornet males from the recent invasive population in Italy. We assessed the importance of nestmateship and female morpho-physiological traits, likely indicators of caste, in determining male attraction towards potential partners. Our results demonstrate that males are more attracted to bigger females with more abundant fat storage, good indicators of female reproductive caste in wasps, regardless of nestmateship. Our findings represent a first step in understanding the reproductive biology of V. velutina nigrithorax in its invasive range, providing a framework for future research in the field to prevent or reduce the species expansion.